2008
DOI: 10.1620/tjem.216.277
|View full text |Cite
|
Sign up to set email alerts
|

Low Visual Acuity is Associated with the Decrease in Postural Sway

Abstract: Vision contributes to upright postural control by providing afferent feedback to the cerebellum. Vision is generally classified into central and peripheral vision, but little is known about the respective role of central and peripheral vision for postural control with different visual acuity levels. This study examined the influence of visual acuity and visual field conditions on upright posture. Eleven males (21.1 ± 2.0 yrs) and 15 females (22.2 ± 2.2 yrs) were classified into high (above 1.0 binocular vision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Much of our knowledge about the relationship between vision and balance has been obtained largely by comparing eyes open and closed conditions, and observing the effects upon body sway (Uchida et al 1979;Hytonen et al 1993;Fujita et al 2005;Rougier and Garin 2006;Guerraz and Bronstein 2008;Uchiyama and Demura 2008). While it has been shown that older adults sway more in response to unexpected eye-movements (Speers et al 2002;van Wegen et al 2002;Monzani et al 2005), the relationship between postural configuration and eyemovement behaviour is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Much of our knowledge about the relationship between vision and balance has been obtained largely by comparing eyes open and closed conditions, and observing the effects upon body sway (Uchida et al 1979;Hytonen et al 1993;Fujita et al 2005;Rougier and Garin 2006;Guerraz and Bronstein 2008;Uchiyama and Demura 2008). While it has been shown that older adults sway more in response to unexpected eye-movements (Speers et al 2002;van Wegen et al 2002;Monzani et al 2005), the relationship between postural configuration and eyemovement behaviour is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…We revealed in our previous study that body sway velocity became lower when participants, who were maintaining an upright standing posture in a dark room, were presented with a visual target as compared to the condition in which they received no visual cue [20]. This suggests that fixation in a dark room has the possibility to contribute to postural stabilisation.…”
Section: Introductionmentioning
confidence: 87%
“…Visual feedback can be integrated with afferent information coming from the vestibular and somatosensory senses, contributing to and improving postural control [16]. In the previous study, as a result of comparing with or without visual feedback, the amount of COP trajectory decreased with feedback [17].…”
Section: Introductionmentioning
confidence: 89%